Dairy Economy of India: Structural Changes in Consumption and Production. (July 2016) - Ohlan, Ramphul
India remains the world's largest producer and consumer of milk. The present study empirically evaluates the transformations in demand and supply of dairy products in India, identifying that the share of dairy products in the food basket has significantly increased among both rural and urban consumers. While demand for dairy products is highly elastic and related to income, the analysis also shows large regional disparities in production and per capita availability of milk in India. After examining various aspects of dairy consumption and production patterns in India, the article also includes policy considerations to improve dairy production. It suggests that to stimulate dairy sector development and reduce inequality in dairy products consumption in India, milk and milk products should be included in the diet provided through the Midday Meal Schemes for primary education children. Overall, to meet the growing demand for dairy products, given their role in food security, the Government of India should continue to aim for sustained growth.